Combating piracy under the United Nations convention on the Law of the Sea 1982 - Ansari, Abdul Haseeb; Win, Kyaw Hla; Hamid, Abdul Ghafur@Khin Maung Sein (Indian Law Institute, New Delhi, India, 2014)
Piracy has long been a serious threat to humankind from the time when people started navigation at seas and it still occurs in various parts of the world despite the efforts being made by the international community. The highest number of attacks occurred as recent as in 2011 ever since IMO started preparing annual report from 1984. Definition of piracy under the primary global anti-piracy instrument, i.e. the UNCLOS 1982, merely codifies customary international law relating to piracy and thus it only provides legal basis to cover traditional piracy. Pirates have taken new trends and employed new methods, which are different from the classical piracy by taking advantage from technological advancements of the modern era. The UNCLOS 1982 piracy regime is too narrow to be effective in combating modern-day piracy and thus there is a need to provide a wide-ranging definition of piracy in which all forms of modern-day piratical attacks can be considered as offences. In suppressing piracy, it is paramount to reexamine the efficacy of the piracy regime under the UNCLOS 1982. Accordingly, the author intents to evaluate its shortcomings and proposes viable solutions. This article critically analyses the essential elements of the definition of piracy, i.e. acts of piracy; private ends; two ships; private ships; and locality of piracy. Moreover, the jurisdiction to seize pirate ships and prosecution of pirates are also examined thoroughly with the intention to contribute in suppressing piracy all over the world.